Anti-adhesion study of three-dimensional reconstructed carbon coatings - Pu, Bei; Deng, Lusha; Lu, Jun; Wei, Liang; Xiong, Xiaoxing (Frontiers in Materials, 2024)
This research study focuses on the investigation of a three-dimensional reconstructed carbon coating based on stainless steel. The investigation encompasses the assessment of surface structure, elemental composition, cytotoxicity, and impact on wound healing.The findings indicate that the carbon coating possesses an approximate thickness of 700 nm, exhibiting a distinctive porous structure. Moreover, the surface water contact angle measures 97.7°, representing a 48.4° increase compared to uncoated stainless steel.Energy-dispersive spectroscopy (EDS) analysis confirms the uniform distribution of diverse elements on the coating's surface. Additionally, X-ray photoelectron spectroscopy (XPS) verifies a substantial carbon accumulation. The electrical resistance of the stainless steel remains largely intact after the application of the coating, as demonstrated by the four-probe method. Notably, ex vivo porcine liver tissue cutting experiments using carbon-coated electrosurgical pencil electrodes showed a significant anti-adhesion effect, with a reduction in tissue adhesions of 81.3%. Furthermore, the MTT test indicates no significant cytotoxicity associated with the carbon coating. Rat skin-cutting experiments further validate that the coating does not impede the process of wound healing. Overall, this study successfully validated the desirable properties of stainless steel-based 3D reconstructed carbon coatings, such as enhanced surface properties, improved anti-adhesion efficacy, negligible cytotoxicity, and compatibility with wound healing. These findings are important for advancing medical device technology and improving patient outcomes.